Generalized soldering of +/- 2 helicity states in D=2+1 - Dalmazi, D. [UNESP]; Mendonca, Elias L. [UNESP] (Amer Physical Soc, 2009)
The direct sum of a couple of Maxwell-Chern-Simons gauge theories of opposite helicities +/- 1 does not lead to a Proca theory in D=2+1, although both theories share the same spectrum. However, it is known that by adding an interference term between both helicities we can join the complementary pieces together and obtain the physically expected result. A generalized soldering procedure can be defined to generate the missing interference term. Here, we show that the same procedure can be applied to join together +/- 2 helicity states in a full off-shell manner. In particular, by using second-order (in derivatives) self-dual models of helicities +/- 2 (spin-2 analogues of Maxwell-Chern-Simmons models) the Fierz-Pauli theory is obtained after soldering. Remarkably, if we replace the second-order models by third-order self-dual models (linearized topologically massive gravity) of opposite helicities, after soldering, we end up exactly with the new massive gravity theory of Bergshoeff, Hohm, and Townsend in its linearized approximation.